2020
DOI: 10.1186/s12889-020-09887-9
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of same-day antiretroviral therapy initiation in retention outcomes among people living with human immunodeficiency virus in Ethiopia: empirical evidence

Abstract: Background In August 2016, Ethiopia endorsed a universal “test and treat” strategy for people living with human immunodeficiency virus (PLHIV) based on World Health Organization recommendation. However, there is limited evidence on the routine application of the same-day “test and treat” recommendation in low-income settings. This study assessed the effect of same-day treatment initiation on individual-level retention at 6- and 12-months follow-up. Methods A multicenter facility-based retrospective cohort stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(40 citation statements)
references
References 44 publications
(76 reference statements)
3
37
0
Order By: Relevance
“…From patient side, some people may need more time to comprehend the result and cope with the news of being HIV positive before deciding to start a lifelong treatment immediately after diagnosis. Additionally, the suboptimal viral load status among same-day group could be related to a higher attrition in this group that has been published elsewhere [18]. In this study, LTFU individuals with no documented viral load result were considered as having high viral load.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…From patient side, some people may need more time to comprehend the result and cope with the news of being HIV positive before deciding to start a lifelong treatment immediately after diagnosis. Additionally, the suboptimal viral load status among same-day group could be related to a higher attrition in this group that has been published elsewhere [18]. In this study, LTFU individuals with no documented viral load result were considered as having high viral load.…”
Section: Discussionmentioning
confidence: 81%
“…This study was part of the study that evaluates the effectiveness of same-day ART initiation in Ethiopia. The detail of the study setting has been published elsewhere [18]. Briefly, this study was conducted at 11 public health facilities in Bahir Dar and Gondar, towns in Amhara region of northwest Ethiopia.…”
Section: Study Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample size of this study was 988 (433 same-day and 555 after 7 days), which includes all eligible PLHIV who were newly diagnosed and started on ART between 20 October 2016 and 18 July 2018 at study sites. 20 We calculated a required sample size of 427 study participants for both groups to be able to detect a 10% absolute difference in the proportion of individuals with optimal adherence between the two groups, based on results from studies conducted in the Amhara region of Ethiopia on self-reported optimal adherence among PLHIV who started ART before universal "test and treat" approach. 23,24 We used P 1 of 98% (proportion of PLHIV having optimal adherence among individuals in the sameday group) and P 2 of 88% (proportion of PLHIV having optimal adherence among individuals in the control group).…”
Section: Study Size and Sampling Methodsmentioning
confidence: 99%